Philosophical Inquiry in the Age of AI and digital technologies: Critical Thinking Pedagogy for Digital Natives - Salem Aladi; Sami Barkah (PT. Pusmedia Group Indonesia, 2026)
Generative AI is used by students as a study and writing tool, which could reshape how they read, argue, and evaluate ideas. This change is important in philosophy courses where learning depends on dialogic inquiry, close reading, and evidence-based reasoning. This study investigates how (AI) influences and reshapes the teaching and learning of philosophical inquiry and critical thinking among digital-native university students. Using mixed-methods that combine pre-test and post-test quantitative assessment with interviews and classroom observations, the research examines the extent to which AI-supported dialogic tasks influence argument identification, fallacy detection, inferential reasoning, and conceptual clarity. Quantitative data were analyzed by comparing pre–post gains within and between an AI-supported group and a traditionally taught control group. A sample of 100 students was divided into an AI-supported group and a traditionally taught control group, with post-test findings showing significantly higher gains for the AI group (d = 2.91), particularly in inferential reasoning and conceptual clarity. Qualitative data from 20 student and 10 instructor interviews show that learners view AI as a cognitive partner that enhances explanatory clarity, expands interpretive possibilities, and increases confidence in constructing arguments, though concerns appear regarding overreliance. Instructor observations corroborate these patterns, indicating shifts in classroom dynamics. The results show greater engagement and question diversity, but diminished persistence when confronting challenging primary texts. The study concludes that while AI can meaningfully improve critical-thinking development in philosophy classrooms, its pedagogical success depends on structured instructor mediation to preserve deep reading, intellectual struggle, and reflective judgment.